Quantitative measurements in obstetric MRI - Tyler, Damian J. (2002)
This thesis describes the development and application of quantitative echo planar magnetic resonance imaging techniques to the study of human placental development in normal and compromised pregnancies. Initially, a method of rapidly and accurately measuring the transverse relaxation time is proposed using a multi-echo measurement sequence. The method is described, validated on CUS04 phantoms and applied in the study of the human placenta and gastric dilution. It is shown that the inversion provided by sinc pulsesis insufficient to generate an accurate measurement but using adiabatic refocusing pulses yields a measurement that is comparable with a single spin echo. Subsequently, a rapid magnetisation transfer method is presented that allows the quantification of the relative size of the bound proton pool. An experimental pulse sequence is proposed, along with a theoretical model, that permits the investigation of the bound proton pool's transition towards the steady state. The sequence and model are validated using agar gel phantoms and shown to agree well with literature values. When applied in the study of the human placenta, it is shown that there is no significant variation in the fitted value of the bound proton pool size with increasing gestational age or in compromised pregnancies. Finally, several methods of measuring the oxygenation level of blood within the human placenta are investigated. The signal intensities of cardiac gated T~• and T~ weighted images acquired at various points in the maternal cardiac cycle are explored but no significant variation is shown through the cycle. A pulsed gradient spin echo sequence that utilises anti-symmetric sensitising gradients is validated and then applied in the human placenta. Oxygenation measurements with this technique are shown to be unfeasible but the potential of the sequence to monitor blood flow in the placenta is demonstrated.